Neurotoxicity of subarachnoid hyperbaric bupivacaine in dogs - Ganem, Eliana Marisa [UNESP]; Vianna, Pedro Thadeu G. [UNESP]; Marques, Mariangela [UNESP]; Castiglia, Yara M. M. [UNESP]; Vane, Luis Antonio [UNESP] (My University, 1996)
Background and Objectives. The study investigated possible neurotoxic effects of increasing concentrations and doses of bupivacaine administered into the subarachnoid space in dogs. Methods. Fifty animals were allocated to five experimental groups: G1, control; G2, 5 mg 0.5 bupivacaine in 10% glucose solution; G3, 10 mg of 1% bupivacaine in 10% glucose solution; G4, 20 mg 2% bupivacaine in 10% glucose solution, and G5, 20 mg 2% bupivacaine in water. After 72 hours of observation, the animals were killed and the spinal cords removed for histologic examination by light microscopy. Results. None of the animals showed any neurologic clinical disturbance following recovery from spinal anesthesia. One case of necrosis of nerve tissue was observed in G3 and four in G4. Conclusions. Increasing concentrations and doses of hyperbaric bupivacaine solutions increased the incidence of nerve tissue damage, which did not occur with hypobaric solutions. These results should contribute to the further understanding of neurologic complications following spinal anesthesia when large doses of local anesthetics in hyperbaric solutions are used.
Keywords: bupivacaine; cauda equina syndrome; neurologic damage; spinal anesthesia